A facile acid induced water-based solvent by improving hydrophobicity for simultaneous remediating total petroleum hydrocarbon, heavy metals and benzo(a) pyrene contaminated soil: Laboratory- and pilot-scale studies. (1st January 2021) - Choong, Choe Earn; Wong, Kien Tiek; Yoon, So Yeon; Kim, Heeyeon; Shin, Mincheol; Chang, Yoon-Young; Yang, Jae-kyu; Kim, Sang-Hyoun; Jeon, Byong-Hun; Yoon, Yeomin; Jang, Min
Abstract: Herein, the partially water-soluble solvent (ethyl-acetate/ethanol/water, designated as EAEW) was applied to remediate complexly contaminated soils by total petroleum hydrocarbons (TPH), heavy metals (HMs) and benzo(a)pyrene (BaP). The hydrochloric acid (HCl) modified EAEW solvent had 95% of TPH and 80% of HMs removal efficiencies at room temperature, making suitable feature for energy saving. The laboratory tests revealed that the optimized condition of washing process was pH 3, soil (g) to solvent (mL) ratio (8:25) and 3 h washing time. Further, the EAEW solvent was regenerated and reused for 3 cycles using a distillation system and high removal efficiencies were kept for TPH (avg. 97.5%) and HMs (avg. 83.6%). As the highlighted finding, the addition of HCl for the EAEW solvent is crucial for highly removing multi-pollutants because HCl can leach HMs and enhance the TPH extraction through suppressing the hydrolysis of EA that can promote higher hydrophobicity. In the pilot-scale system, a sequential washing process by the use of HCl modified EAEW solvent followed by 0.1 M HCl removed 74.2–91% HMs and 96% BaP, satisfying all Korean standard (KS) guidelines. More importantly, 95.5% of EA/ethanol was recovered by the distillation system operated at 60 °C and 500 mm Hg pressure for 15 min. Not only proven effectiveness of EAEW solvent, but also its high recovery and environmental-friendly property could give a high potential for feasible on-site application for multi-polluted soil remediation. Graphical abstract: Image 1 Highlights: The acidified EAEW solvent showed effective removal efficiencies for TPH, BaP and HMs contaminated soil. The addition of HCl to the EAEW solvent significantly enhanced the extraction performance. The presence of HCl reducing the hydrolysis of EA and increasing the hydrophobicity of EAEW solvent. The EAEW solvent was perfectly regenerated and reused for 3 cycles.